2015
DOI: 10.1007/s00296-015-3302-5
|View full text |Cite
|
Sign up to set email alerts
|

How many patients with post-chikungunya chronic inflammatory rheumatism can we expect in the new endemic areas of Latin America?

Abstract: Post-chikungunya chronic inflammatory rheumatism (pCHIK-CIR) is one of the consequences that are impacting new endemic countries, such as those in the Americas. The relative frequency of pCHIK-CIR is highly variable, ranging from 14.4 % to 87.2 % (including variable number of patients and follow-up times). Based on those non-weighted values, it is difficult to estimate which would be the expected number of patients with CHIK who will develop CIR. For these reasons, we modeled weighted estimations based on pool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
55
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 17 publications
6
55
0
5
Order By: Relevance
“…55,56 Nevertheless, the Colombian burden of CHIKF in terms of disability-adjusted life years and the cost of treatment should be estimated along with studies throughout the Americas to determine if the Asian CHIKV lineage differs from the IOL in virulence. [57][58][59][60] Infections in Colombia with CHIKV could also be influenced by the presence of other pathogens. The alphaviruses MAYV and CHIKV, closely related in the Semliki Forest complex, could cross-protect to some degree.…”
Section: Discussionmentioning
confidence: 99%
“…55,56 Nevertheless, the Colombian burden of CHIKF in terms of disability-adjusted life years and the cost of treatment should be estimated along with studies throughout the Americas to determine if the Asian CHIKV lineage differs from the IOL in virulence. [57][58][59][60] Infections in Colombia with CHIKV could also be influenced by the presence of other pathogens. The alphaviruses MAYV and CHIKV, closely related in the Semliki Forest complex, could cross-protect to some degree.…”
Section: Discussionmentioning
confidence: 99%
“…Until today, no observational studies in the region have described its prevalence, but recent estimations indicated that probably about 48 % of infected people in Latin America in a median of 20 months would develop it [2]. In this scenario, where over one million cases of CHIK were reported in the Americas during 2014, observational studies describing this rheumatologic consequence are urgently needed.…”
mentioning
confidence: 97%
“…Among the studies assessing pCHIK-CIR, its relative frequency is highly variable, ranging from 14.4 to 87.2 % (including variable number of patients and follow-up times) [2,4,5]. Unfortunately, only studies assessing acute polyarthralgia (96 %) and arthritis (47 %) have been published in Latin America during the current CHIK epidemics [6], even without laboratory serological or molecular confirmation, which is highly relevant [7].…”
mentioning
confidence: 98%
“…Although viremia is usually cleared 5-7 days after infection and most acute symptoms resolve within 2 weeks, rheumatic manifestations can persist for months to years in a subset of individuals (7-10, 37, 103, 126, 127). The percentage of CHIKV-infected patients reported to develop protracted illness varies greatly (~14% to ~87%), but an average prevalence of approximately 48% among infected patients has been estimated (128). Risk factors for chronic CHIKV disease include age (>45 years), preexisting chronic inflammatory arthropathy, and severity of symptoms during the acute phase (129,130).…”
Section: Disease Mechanisms and Host Immune Responsesmentioning
confidence: 99%